Uptake of poly-dispersed single-walled carbon nanotubes and decline of functions in mouse NK cells undergoing activation. (2nd September 2016) - Alam, Anwar; Puri, Niti; Saxena, Rajiv K.
Abstract: The interaction of poly-dispersed acid-functionalized single-walled carbon nanotubes (AF-SWCNT) with NK cells undergoing activation was examined. Exposure to AF-SWCNT during NK activation in vitro by interleukin (IL)-2, and in vivo by Poly(I:C) significantly lowered cytotoxic activity generated against YAC-1 tumor cells. Recoveries of spleen NK1.1 + cells as well as the activated subset of NK cells (NK1.1 + CD69 + cells) were significantly reduced by the AF-SWCNT exposure. The proportion of apoptotic NK cells (NK1.1 + phosphatidylserine + ) in the spleen cell preparations activated in vitro was also significantly elevated. Expression levels of CD107a [for assessing NK cell degranulation] as well as of FasL marker [mediating non-secretory pathway of NK cell killing] were significantly lower in cells exposed to AF-SWCNT during the activation phase. Intracellular levels of interferon (IFN)-γ and tumor necrosis factor (TNF)-α in the cells were also significantly reduced. Fluorescent AF-SWCNT (FAF-SWCNT) were internalized by the NK cells and uptake was significantly greater in activated cells. Confocal microscopy indicated the internalized FAF-SWCNT were localized to the cytoplasm of the NK cells. These results indicated that AF-SWCNT were internalized by NK cells and caused a general down-regulation of a variety of parameters associated with NK cell cytotoxicity and other cellular functions.